The Old-Age Security Motive for Fertility: Evidence from the Extension of Social Pensions in Namibia - Pauline Rossi; Mathilde Godard (Tinbergen Institute, 2019)
The old-age security motive for fertility postulates that people's needs for old-age support raise the demand for children. We test this widespread idea using the extension of social pensions in Namibia during the nineties. The reform eliminated inequalities in pension coverage and benefit across regions and ethnic groups. Combining differences in pre-reform pensions and dfferences in exposure across cohorts, we show that pensions substantially reduce fertility, especially in late reproductive life. This article provides the first quasi-experimental quantification of the old-age security motive. The results suggest that improving social protection for the elderly could go a long way in fostering fertility decline in Sub-Saharan Africa.
Keywords: D15; H55; I38; J13; O15; O55; 330; Fertility; Old-age pensions; Social security; Africa; Difference-in-differences